What Drives the Global Land Rush? - Selod, Harris (IMF Working Papers; Working Paper ;, 2011)
This paper studies the determinants of foreign land acquisition for large-scale agriculture. To do so, gravity models are estimated using data on bilateral investment relationships, together with newly constructed indicators of agro-ecological suitability in areas with low population density as well as indicators of land rights security. Results confirm the central role of agro-ecological potential as a pull factor. In contrast to the literature on foreign investment in general, the quality of the business climate is insignificant whereas weak land governance and tenure security for current users make countries more attractive for investors. Implications for policy are discussed.